2021
DOI: 10.1200/jco.2021.39.15_suppl.e21010
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of KRAS, TP53, STK11 and KEAP1 mutations and the influence of the NLR in NSCLC patients treated with immunotherapy.

Abstract: e21010 Background: ICIs changed the way NSCLC is treated, but not all patients benefit from it. PD-L1 level is used to predict response to therapy, but its performance is sub-optimal. KRAS is important in NSCLC tumorigenesis, but the impact of its mutations in patients treated with ICIs is unclear. Similarly, studies evaluating co-mutations in TP53, STK11 and KEAP1 as well as the NLR showed that they may predict the benefit of ICIs. Methods: We conducted a retrospective study including all consenting patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There have been preliminary reports of comutations in STK11, KEAP, and TP53 modulating the responsiveness of patients with KRAS G12C alterations to either KRAS G12C inhibitors or to standard-of-care immunotherapy and chemotherapy. 22,[33][34][35][36][37][38][39][40][41][42][43][44] However, this is beyond the scope of this review and is not discussed further here.…”
Section: Mechanisms Of Primary Resistancementioning
confidence: 99%
“…There have been preliminary reports of comutations in STK11, KEAP, and TP53 modulating the responsiveness of patients with KRAS G12C alterations to either KRAS G12C inhibitors or to standard-of-care immunotherapy and chemotherapy. 22,[33][34][35][36][37][38][39][40][41][42][43][44] However, this is beyond the scope of this review and is not discussed further here.…”
Section: Mechanisms Of Primary Resistancementioning
confidence: 99%
“…Some studies have demonstrated that co-mutations in STK11 , KEAP1 , and TP53 could modulate the responsiveness of patients with KRAS alterations to either KRAS G12C inhibitors or to immunotherapy ( 14 16 , 18 , 95 ). Proulx-Rocray and colleagues (2021) showed that the presence of STK11 and/or KEAP1 mutations was associated with a negative impact on survival when compared with wild-type NSCLC patients treated with immune check point inhibitors ( 96 ). These authors also reported that in patients harboring KRAS mutation, improved prognosis was observed in STK11+KEAP1 wild-type tumors but not in STK11+/-KEAP1 mutant tumors.…”
Section: Mechanisms Of Resistance To Kras Inhibitionmentioning
confidence: 99%
“…There are indications that STK11 and KEAP1 mutations are significant adverse predictors for the efficacy of immune check point inhibitor (ICIs) therapy in NSCLC patients with KRAS mutations [49]. However, the neutrophil-lymphocyte ratio (NLR) is impacted by STK11 but not by KEAP1 mutations.…”
Section: Induces Apoptosis Arrests the Cell Cycle Atmmentioning
confidence: 99%
“…It suggests differences in the immunotherapy resistance mechanism connected with the presence of both mutations. The authors concluded that KRAS mutations could be associated with improved survival in NSCLC patients treated with immunotherapy in the absence of mutations in the STK11 and KEAP1 genes in tumor cells [49].…”
Section: Induces Apoptosis Arrests the Cell Cycle Atmmentioning
confidence: 99%